Systematic review of the alkaloid constituents in several important medicinal plants of the Genus Corydalis. (March 2021) - Deng, Ai-Ping; Zhang, Yue; Zhou, Li; Kang, Chuan-Zhi; Lv, Chao-Gen; Kang, Li-Ping; Nan, Tie-Gui; Zhan, Zhi-Lai; Guo, Lan-Ping; Huang, Lu-Qi
Abstract: The genus Corydalis is a botanical source of various pharmaceutically active components. Its member species have been widely used in traditional medicine systems in Southeast Asia, especially in China for thousands of years. They have been administered to treat the common cold, hypertension, hepatitis, hemorrhage, edema, gastritis, cardiovascular and cerebrovascular diseases, and neurological disorders. Analgesia is the most important effect of Corydalis products, which are relatively non-addictive and associated with low tolerance compared with other analgesics. Certain Corydalis species are rich in alkaloids, which have strong biological activity, and also contain coumarins, flavonoids, steroids, organic acids and other chemical components. These constituents have pharmacological efficacy against diseases of the nervous, cardiovascular and digestive systems. Numerous investigations have been performed on these plants and their components. Here, we systemically summarized the chemical constituents of important medicinal member species of Corydalis that have been reported since 1962. A total 381 alkaloids were enumerated, including 117 quaternary isoquinoline type, 60 Benzophenanthridine type, 37 aporphine type, 10 protopine type, 59 phthalide isoquinoline type, 52 simple isoquinoline-type, 25 lignin amides and 21 other alkaloids. Thus, we have provided a basis for further explorations into the pharmacologically active constituents of Corydalis sp .(Papaveraceae) to develop medicines that exert strong effects, are relatively non-addictive, and result in few side effects. Graphical abstract: Image 1 Highlights: Alkaloids of important medicinal member species of Corydalis that have been reported since 1962 were summarized. A total of 381 alkaloids reported in Corydalis until now. Alkaloids were the most important compounds with diversity structures in Corydalis.